Does a manual therapy approach improve the symptoms of functional constipation? A systematic review of the literature. (June 2020) - Erdrich, Leon M.; Reid, Duncan; Mason, Jesse
Abstract: Background: Functional constipation is highly prevalent and places a significant burden on healthcare systems around the world. Manual therapy is a commonly used intervention, however to date there has not been a systematic review that critically appraises a wide range of manual therapy disciplines. Objectives: To systematically review the literature and analyse the methodological quality of all included studies, and to provide an overall level of evidence analysis. Methods: A database search was completed to identify eligible studies that were published from database creation to July 2018. The relevant characteristics of each study were extracted, and each study was assessed for methodological quality with a modified version of the Downs and Black appraisal tool. Results: Seven studies fulfilled the inclusion criteria and were assessed for methodological quality. One study was found to have 'strong' methodological quality, five were of 'moderate' quality, and one was of 'low' quality. All studies reported consistent findings regarding their individual primary outcome measures. Overall level of evidence for the use of manual therapy as an intervention for constipation was found to be 'moderate'. Conclusions: There is moderate quality evidence for the use of manual therapy as an intervention for constipation. The review identified several themes that can guide future research on this topic, including intervention type and frequency, reporting quality, mechanism of effect, and variability of outcome measures.